Strong linkages between depth, longevity and demographic stability across marine sessile species - Montero-Serra I. (2018)
Understanding the role of the environment in shaping the evolution of life histories remains a major challenge in ecology and evolution. We synthesize longevity patterns of marine sessile species and find strong positive relationships between depth and maximum lifespan across multiple sessile marine taxa, including corals, bivalves, sponges and macroalgae. Using long-term demographic data on marine sessile and terrestrial plant species, we show that extreme longevity leads to strongly dampened population dynamics. We also used detailed analyses of Mediterranean red coral, with a maximum lifespan of 532 years, to explore the life-history patterns of long-lived taxa and the vulnerability to external mortality sources that these characteristics can create. Depth-related environmental gradients-including light, food availability, temperature and disturbance intensity-drive highly predictable distributions of life histories that, in turn, have predictable ecological consequences for the dynamics of natural populations. © 2018 The Author(s) Published by the Royal Society. All rights reserved.